Prospek Penerapan Moslem Friendly Tourism pada Tempat Wisata Rammang-Rammang Kabupaten Maros - Wildan Hilmawan (Bulletin of Community Engagement, 2024)
The main problem of this research is how the prospect of implementing Moslem Friendly Tourism in Rammang-Rammang tourist attractions, Maros Regency. The main problem is further elaborated into several sub-problems, namely: First, how do tourism managers understand Moslem Friendly Tourism. Second, how is the potential application of Moslem Firendly Tourism to Rammang-Rammang tourist attractions. Third, how does tourism respond to community services or managers in a Moslem Friendly Tourism manner. This type of research is qualitative research. The data source comes from primary data, which is 15 people with the manager as the key informant and secondary data comes from various sources, namely books, journals and other research. The data collection method used is by conducting observations, interviews and documentation.  The results of this study show that the condition of Rammang-Rammang tourism has various aspects of Muslim needs that support so that it is a positive thing for the implementation of Moslem Friendly Tourism. In addition, the management is quite open to the concept of Moslem Friendly Tourism, remembering that 100% of the villagers adhere to Islam, so it is very easy to accept the concept. However, the role of the government in terms of providing education is still quite weak, so the concept is not implemented.